Tingkah Laku Pembelian Komputer Riba dalam Kalangan Pelajar Institut Pengajian Tinggi Awam (IPTA) - Ishak, Nuraini; Md Jusoh, Zuroni; Mohamed, Rozita Naina (Malaysian Consumer and Family Economics Association (MACFEA), 2023)
Consumer behaviour towards laptop purchases is a major focus for market analysts, vendors and key drivers in consumer purchases. The purpose of the study is to determine the relationship between variables such as attitude, knowledge, willingness to pay and perception of control with computer purchasing behaviour among IPT students. This study is based on a survey of 200 consumers on laptop purchasing behaviour using simple random sampling. The results of the study show that the variables of attitude and perception of behavioural control have a significant and positive relationship with the behaviour of computer purchases, namely (r=0.004, p>0.05) and (r=0.049, p>0.05). While the variable of knowledge and willingness to pay in the purchase of a laptop computer was found to have no significant relationship with the computer purchase behaviour which is (r=0.347, p<0.05) and (r=0.700, p<0.05). This is because students are more likely to prioritize quality and reliability before and during the purchase of a laptop.